Legal Rules Concerning Shoot to Death for Criminal Acts of Terrorism in the Perspective of the Principle of the Prejudiction of Innovality - Moh. Lubsi Tuqo Romadhan; Nur Khotimah; Shinta Widhaningroem; Tekun Ibadata (Musamus Law Review, 2021)
The state in carrying out the life of the nation and state faces threats that come from within the country and abroad. This study aims to find out the legal rules regarding shooting to death for perpetrators of criminal acts of terrorism in the perspective of the principle of the presumption of innocence, where this case has always been a hot issue in Indonesia, especially when we associate shooting to death or being shot on the spot for perpetrators of criminal acts of terrorism with the principle of presumption of innocence. This research is normative in nature with reference to existing books, journals, and laws and regulations. There are several legal rules that form the basis for doing so/shooting death against terrorism crimes are: Article 48 of the Criminal Code, In Article 49 paragraph (1) of the Criminal Code, In Article 51 of the Criminal Code paragraph (1), National Police Chief Regulation Number 8 of 2009 concerning Implementation of Human Rights Principles and Standards. The principle of presumption of innocence also places him in the Burden of Proof or the burden of proof and it is the duty of the public prosecutor to prove the defendant's guilt, unless the proof of Insanity is imposed on the defendant or the law provides strict provisions for reverse proof. The application of the principle of presumption of innocence must also always uphold human rights that must be respected by everyone.